2016
DOI: 10.18632/oncotarget.7894
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback regulation between IL10 and EGFR promotes lung cancer formation

Abstract: The role of IL10 in the tumorigenesis of various cancer types is still controversial. Here, we found that increased IL10 levels are correlated with a poor prognosis in lung cancer patients. Moreover, IL10 levels were significantly increased in the lungs and serum of EGFRL858R- and Kras4bG12D-induced lung cancer mice, indicating that IL10 might facilitate lung cancer tumorigenesis. IL10 knockout in EGFRL858R and Kras4bG12D mice inhibited the development of lung tumors and decreased the levels of infiltrating M2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 40 publications
0
27
1
Order By: Relevance
“…Whereas our data demonstrate a therapeutic role for IL-10 in the LSLKras model of lung tumorigenesis, others have found that IL-10-producing tumor cell lines can display enhanced growth in mice (36)(37)(38). This observation is likely associated with the early paracrine effects of IL-10 on the injected tumor cells and/or local angiogenic activity in the absence of a preexisting immune response.…”
Section: Discussioncontrasting
confidence: 65%
“…Whereas our data demonstrate a therapeutic role for IL-10 in the LSLKras model of lung tumorigenesis, others have found that IL-10-producing tumor cell lines can display enhanced growth in mice (36)(37)(38). This observation is likely associated with the early paracrine effects of IL-10 on the injected tumor cells and/or local angiogenic activity in the absence of a preexisting immune response.…”
Section: Discussioncontrasting
confidence: 65%
“…This effect was observed by engagement of CD81 at a higher concentrations (10 or 30 μg/mL) of JS‐81 antibody alone, but was negligible at a lower CD81 engaging JS‐81 antibody concentration (<10 μg/mL). IL‐10 and EGFR regulate each other through positive feedback, and IL‐10 subsequently activates Stat3 signaling pathways. CBH‐2 mAb inhibits E2‐CD81 binding.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of Akt is associated with a reduction in M2‐associated gene expression, indicating that activation of Akt is involved in macrophage polarization to the M2 phenotype. IL‐10 and EGFR regulate each other through positive feedback, and IL‐10 subsequently activates Stat3 signaling pathways. Furthermore, induction of IL‐10 in macrophages is associated with Akt activation .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, IL-10 signals that are required for EGFR induction has also been reported. Of note, IL-10-induced EGFR expression requires activation and recruitment of Src to IL-10 receptor subunit α, which increases JAK1/STAT3 signalling activity and results in the expression of EGFR [56]. …”
Section: Functional Molecules Expressed or Produced By ‘Repair’ Tregsmentioning
confidence: 99%